Developing efficient traffic safety law enforcement programmes in rapidly developing countries - George Yannis (568695) (2015)
This presentation focusses on the analysis of the fundamental characteristics of traffic enforcement systems for the improvement of traffic safety and the development of a framework of principles and proposals for enforcement programs of selected traffic violations in rapidly developing countries. The methodology used includes a wide review of international literature as well as processing, evaluation and ranking of particular enforcement actions of traffic violations such as speeding, non-use of seat belt and helmet, drinking and driving and mobile phone use. A framework of principles is developed along with special actions within the integrated enforcement programs of selected violations with special emphasis to the particular driver behaviour and safety characteristics in the rapidly developing countries (pedestrian and motorcycle safety, inadequate infrastructure, lack of road safety culture). Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.60